Posterior midline and ventral parietal activity is associated with retrieval success and encoding failure - Daselaar, Sander M.; Prince, Steven E.; Dennis, Nance A.; Hayes, Scott M.; Kim, Hongkeun; Cabeza, Roberto (Frontiers in Human Neuroscience, 2009)
The ventral part of lateral posterior parietal cortex (VPC) and the posterior midline region (PMR), including the posterior cingulate cortex and precuneus, tend to show deactivation during demanding cognitive tasks, and have been associated with the default mode of the brain. Interestingly, PMR and VPC activity has been associated with successful episodic retrieval but also with unsuccessful episodic encoding. However, the differential contributions of PMR and VPC to retrieval vs. encoding has never been demonstrated within-subjects and within the same experiment. Here, we directly tested the prediction that PMR and VPC activity should be associated with retrieval success but with encoding failure. Consistent with this prediction, we found across five different fMRI experiments that during retrieval, that activity in these regions is greater for hits than misses, whereas during encoding, it is greater for subsequent misses than hits. We also found that these regions overlap with the ones that show deactivations during conscious rest. Our findings further aid in clarifying the role of the default mode regions in learning and memory.